Pengaruh Penggunaan Media Sosial terhadap Kreativitas Peserta Didik di Jurusan Fesyen Desain dan Kreasi ESMOD Jakarta : [The Influence of Social Media Usage on Student Creativity in the Fashion Design and Creation Department, ESMOD Jakarta] - Risanti Intan Al Baluni; Gavrielin Ginarid; Sesilia Fajar Handayani (Jurnal Teropong Pendidikan, 2025)
Technological advancements have introduced the concept of 21st century learning that integrates technology to promote critical and creative thinking. Data shows that 167 million people in Indonesia use social media, with 41.9% aged 13-24 years old. This study aims to analyze the influence of social media use on students' creativity in learning and identify the most influential platforms, with a focus on Instagram and TikTok. This study uses quantitative research methods with correlation data analysis techniques, correlation coefficients, and categorization. This research uses an instrument in the form of a questionnaire that was distributed to 50 fashion design students at ESMOD Jakarta. The results show that the use of social media has a positive influence on the creative process of students, although the influence is very weak which can be seen from the beta coefficient (β) value of 0.09 and the regression value of 0.13, as well as the low determination coefficient (R²) of 0.02. In addition, the results of the T-count value < the T-table (0.52 < 1.68) show that there is not enough evidence to state that there is a significant difference in creativity between Instagram and TikTok users. So, it can be concluded that although social media has a very weak positive effect on students' creativity, there is no significant difference between Instagram and TikTok users. Both platforms contribute almost equally, and other factors may play a more significant role in boosting students' creativity.